Breast‐feeding regulates immune system development via transforming growth factor‐β in mice pups. Issue 3 (25th March 2018) - Sakaguchi, Keita; Koyanagi, Akemi; Kamachi, Fumitaka; Harauma, Akiko; Chiba, Asako; Hisata, Ken; Moriguchi, Toru; Shimizu, Toshiaki; Miyake, Sachiko
Abstract: Background: Breast milk contains important nutrients and immunoregulatory factors that are essential for newborn infants. Recently, epidemiological studies suggested that breast‐feeding prevents a wide range of infectious diseases and lowers the incidence of infant allergic diseases. Methods: To examine the effects of breast milk on immunological development in infancy, we established an artificial rearing system for hand‐feeding mice and compared mouse pups fed with either breast milk or milk substitute. All mice were killed at 14 days of age and immune cells in the thymus, spleen, and small intestine were examined on flow cytometry. Results: The number of thymocytes was higher whereas that of total immune cells of peripheral lymphoid tissues was lower in mice fed breast milk compared with milk substitute‐fed mice. In peripheral lymphoid tissues, the proportion of B cells was higher and that of CD8 + T cells, macrophages, dendritic cells, and granulocytes was significantly lower in breast milk‐fed mice. The same alteration in immune cells of the thymus and peripheral lymphoid tissues in milk substitute‐fed mice was also observed in pups reared by mother mice treated with anti‐transforming growth factor‐β (anti‐TGF‐β) monoclonal antibody. Conclusions: Breast milk regulates the differentiation and expansion of innate and adaptive immune cells partly due to TGF‐β. Hence, TGF‐β in breast milk may be a new therapeutic target for innate immune system‐mediated diseases of infancy.